2018
DOI: 10.7150/jca.26155
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of PD-L1 expression in resected lung adenocarcinoma and potential molecular mechanisms

Abstract: Background: The prognostic role of PD-L1 expression in surgically resected lung adenocarcinoma (ADC) remains controversial. The present study was aimed to clarify the role of PD-L1 expression in predicting prognosis and to investigate its biological function in ADC.Materials and Methods: The association between PD-L1 expression and clinical outcomes in patients with resected ADC was analyzed using immunohistochemistry (IHC) in our cohort (n=104), externally validated by a meta-analysis of 13 published studies.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 50 publications
2
3
0
Order By: Relevance
“…Our results are consistent with other meta-analyses investigating the prognostic impact of PD-L1 tumor expression in NSCLC, all of which have found PD-L1 positivity to be inversely associated with survival (58)(59)(60)(61)(62). However, this is the first meta-analysis to focus only on resectable NSCLC tumors, and to exclude studies with tumors of patients diagnosed with metastatic disease.…”
Section: Discussionsupporting
confidence: 90%
“…Our results are consistent with other meta-analyses investigating the prognostic impact of PD-L1 tumor expression in NSCLC, all of which have found PD-L1 positivity to be inversely associated with survival (58)(59)(60)(61)(62). However, this is the first meta-analysis to focus only on resectable NSCLC tumors, and to exclude studies with tumors of patients diagnosed with metastatic disease.…”
Section: Discussionsupporting
confidence: 90%
“…As regards tumor subtype, the present results showed that PD-L1 TIIC overexpression in adenocarcinoma was associated with poor DFS. This finding is consistent with a meta-analysis ( 35 ) and a cohort study ( 36 ) on PD-L1 in TC in pulmonary adenocarcinoma. However, the present study demonstrated that PD-L1 TIIC expression was associated with improved OS for patients with pulmonary squamous cell carcinoma.…”
Section: Discussionsupporting
confidence: 92%
“…The introduction of immune checkpoint inhibitors (ICIs) into breast oncology has been limited when compared to other cancers such as non-small cell lung (NSCLC), malignant melanoma, bladder and rectal cancers [92][93][94][95]. Currently, the IMPASSION 130 and Keynote 522 trials indicate promise with respect to the role of ICIs in treating TNBC in the early-stage (HR: 0.63, 95% CI: 0.43-0.99) and metastatic settings (HR: 0.80, 95% CI: 0.69-0.92) for combined ICI and conventional chemotherapy compared to placebo and chemotherapy [96,97].…”
Section: Ki-67 and Triple Negative Breast Cancermentioning
confidence: 99%